Nutrient Profiles of Dishes Eaten by High Salt Consumers and Adequate Salt Consumers in the 2013–2018 National Health and Nutrition Survey, Japan. (7th June 2021) - Takimoto, Hidemi; Okada, Emiko; Takebayashi, Jun; Tada, Yuki; Yoshizaki, Takahiro; Yokoyama, Yuri; Ishimi, Yoshiko
Abstract: Objectives: Dish based nutrient profile analyses are essential in setting goals to achieve a balanced diet. The Japanese enjoy longevity, but their current diet is still high in salt, which was 10.1g/day among adults in the 2019 National Health and Nutrition Survey. In 2013, the Japanese government's "Health Meal" proposed the salt content of 3g/650 kcal per meal. However, studies are scarce regarding the nutrient profiles of the dishes eaten by the general population, especially who exceed the current standard. In order to examine the current achievement status and related nutritional problems among a nationally representative sample, we conducted the secondary analyses of the 2013–2018 National Health and Nutrition Survey data. Methods: Dietary data from 35, 915 participants in the 2013–2018 National Health and Nutrition Survey aged 18–74 years who ate three meals on the survey day, were applied for analyses. We extracted 554, 257 dishes from each meal, and categorized them according to the definition of "staple dish" (grain dish), "main dish"(meat, fish, eggs, or beans), and "side dish"(vegetables, seaweeds, potatoes, or mushrooms) shown in the 2005 "Japanese Food Guide Spinning Top". Participants were grouped as "high salt" consumers if their intake were 3g/650kcal or higher, and "adequate" consumers if they consumed less. The nutrient profile of each dish category was compared between the two groups by using the Wilcoxon's signed rank test. Results: 22 300 participants were identified as "high salt" and 13 615 as "adequate". The mean age of the "high salt" group (53.2 years) was higher than the "adequate" group (50.5 years), but their mean energy intake was similar (1901 and 2081 kcal/day, respectively). The mean salt intake in the "high salt" group was 11.8 g/day and the "adequate" group was 7.7 g/day. Among the dishes, 59 936 were categorized as "staple dish", 47 081 as "main dish", 45 828 as "side dish", 30 151 as "combined dish", and 371 261 as "miscellaneous". Except for "staple dish", dishes consumed by the "high salt" group were significantly low in energy and fat but high in salt, compared to the "adequate". Conclusions: Older participants were more likely to consume dishes high in salt, but low in fat. Examples of balanced dishes low in both salt and fat could be proposed for further diet modification. Funding Sources: Ministry of Health, Labour and Welfare research grant.